A resilience-based approach in managing the closure and abandonment of large mine tailing ponds - Dragan Komljenovic; Lazar Stojanovic; Vladimir Malbasic; Aleksandar Lukic (International Journal of Mining Science and Technology, 2020)
Mining tailing ponds are large infrastructure objects whose life cycle spans over several decades. They are indispensable for certain types of mines where technological process produces and rejects mud. They also have potential to generate risks for human life, property and environment. For that reason, it is essential to adequately manage them throughout all the stages of their life cycle. The phase of their closure and abandonment is less studied and understood. The paper proposes a holistic resilience-based approach for analyzing this phase of their life cycle. The proposed methodology is validated through a case study at an actual surface iron ore mine in Bosnia and Herzegovina.